Achieving workers' rights in the global economy (Ithaca, NY., 2016)
"The world was shocked in April 2013 when more than 1,100 garment workers lost their lives in the collapse of the Rana Plaza factory complex in Dhaka. It was the worst industrial tragedy in the two-hundred-year history of mass apparel manufacture. This so-called accident was, in fact, just waiting to happen, and not merely because of the corruption and exploitation of workers so common in the garment industry. In Achieving Workers’ Rights in the Global Economy, Richard P. Appelbaum and Nelson Lichtenstein argue that such tragic events, as well as the low wages, poor working conditions, and voicelessness endemic to the vast majority of workers who labor in the export industries of the global South arise from the very nature of world trade and production. Given their enormous power to squeeze prices and wages, northern brands and retailers today occupy the commanding heights of global capitalism. Retail-dominated supply chains—such as those with Walmart, Apple, and Nike at their heads—generate at least half of all world trade and include hundreds of millions of workers at thousands of contract manufacturers from Shenzhen and Shanghai to Sao Paulo and San Pedro Sula. This book offers an incisive analysis of this pernicious system along with essays that outline a set of practical guides to its radical reform."